Connectedness With Nearby Nature and Well-Being - Nisbet, Elizabeth K.; Shaw, Daniel W.; Lachance, Danielle G. (Frontiers in Sustainable Cities, 2020)
Trees are an integral and salient feature of the natural environment with multiple benefits for environmental and human health. Little is understood, however, about how connectedness with trees or other features of nature (e.g., wildlife) are associated with human health perceptions and well-being. Similarly, research on links between neighborhood trees and nature connectedness is lacking. Community participants (n = 102 older adults, Mage = 61.56, SD = 9.71) in Peterborough, Canada completed questionnaires related to general health (perceived), subjective well-being, interconnectedness with nature, and other demographics. A subsample of participants (n = 36) provided postal codes that allowed for the tree canopy sampling of four neighborhoods. People living near trees reported better mental health perceptions (GHQ-12) and a greater sense of connectedness to the natural world around them. Connectedness with trees, wildlife, and nature was associated with better psychological well-being and less mental distress. This sense of connection was still related to better mental health—more positive moods and feelings of vitality—when controlling for age, income, and neighborhood connectedness. Trees are an integral part of communities and are a cost-effective way of enhancing health as well as mitigating the effects of climate change. Cultivating connectedness with specific elements of the natural environment may help to promote greater environmental concern and behavior, while providing a positively-framed motivation for such action.